MODEL PENGELOLAAN DAN PENGEMBANGAN BANDHA WAKAF MASJID AGUNG SEMARANG - Nurodin Usman (Universitas Muhammadiyah Ponorogo, 2013)
This study describes the management and developmentmodels of bandha waqf Masjid Agung Semarang which has a land area of 119.1270 hectares endowments. Historically, bandha waqf has undergone a process of exchange-bolsters the controversial and spawned a unique form of management, which is managed by three different agencies with no unified management system. According to KMA Number 92 Year 1962, the party who was appointed as manager (nazhir) is a Mosque Welfare Agency (Badan Kesejahteraan Masjid/BKM) Semarang. But in fact, most of bandha waqf Masjid Agung Semarang are managed by BKM, Executive Board of Masjid Agung Semarang, and Executive Board of Masjid Agung Jawa Tengah.Management of bandha waqf can be divided into two forms of endowments or waqf, the consumptive waqf and the productive waqf. Each form is managed with many models, such as the management of endowments for the benefit of bandha waqf for worship, preaching, education, health, and economic empowerment through business units. The management of bandha waqf has set an agenda of development expected to improve the performance of bandha waqf so as to realize the goal. Some bandha waqf asset have developed economically through the efforts of businesses such as gas stations (SPBU) has been got certificate of Pasti Pas and many facilities of business in the Masjid Agung Jawa Tengah. The others, through diversification techniques, bandha waqf currently have more pattern models of business. Nevertheless, up to now, the management and development of bandha waqf has not shown the expected results due to facing many obstacles, especially the management problems that have not been applying the principles of good waqf governance, such as transparency, accountability, independence, fairness, and responsibility. The management of bandha waqf also face problems of conflicts of interest between managers which potentially lose the trust of stakeholders. Therefore, it is important that waqf managed and developed by the human resources that have a good vision of entrepreneurship, have multiple intelligences that can minimize conflicts possibly occur, and have the ability to establish networking with stakeholders.